Evaluación de calidad Bromatológica de Grasa y Proteína obtenida de Larva de Mosca (doméstica), para un uso Sostenible en la Industria Alimenticia Pecuaria - Garzón Castillo, Lenin Shampiel. (2019)
Insects are a sustainable alternative that has been found as an animal feed source due to its high protein and fat content. Locally, bromatology information of fly larva and its potential for livestock use is not known. Insect production can be based on dead protein recycling (dead birds, slaughterhouse waste, organic material with high protein content). Biorecyclers were designed and built to reduce the decomposition time of bio- waste and produce fly larva. It was considered the fly larva production to determine its protein and lipid profile, towards a sustainable alternative feed quality in the livestock food industry. This research determined the fly larva bromatological quality, it estimated the conversion efficiency of bio- waste into protein and live fat, determined the domestic larva proportions as a sustainable alternative in the livestock feed industry. Larva drying carried out for ten days until reaching a range of 12-14 % humidity. The protein content determined by Kjedahl method and the fat content by applying Soxhlet method. 1, 26 kg of fly larva obtained in the experiment. Bio- waste conversion to live larva showed an efficiency of 12,7 %. In addition, the calcium, potassium and iron contents in the larvae were determined. It found that fly larvae have a high nutritional value with 49, 03 % of protein and 35, 06 % of lipids. Fly larvae show a higher quality than fishmeal, so it would be considered a sustainable alternative in the livestock food industry